AKUNTANSI DALAM PERSEPSI SYRIAH ISLAM - Hastuti Olivia (Program Studi Akuntansi Fakultas Ekonomi UMN AL Washliyah, 2020)
Accounting in developing Islamic shari‟ah perspective, in line with the population of Muslims and Islamic banks in the country, accounting also be effected. This is very likely due to the form of accounting itself heavily influenced on the one hand the environment, on the other hand after accounting molded by the environment, the accounting will affect the environment. This is a very large role of accountants in conducting scientific development of Islamic accounting and accounting- based escort the Islamic shari‟a in the level of implementation. In-country non- Muslim countries Islamic financial institution is growing very rapidly, such a s: Franch, Australia, USA, UK, Switzerland, and others. In the context of Indonesia by the Indonesian Institute that the economic system and the business system based on Islamic sharia growing rapidly in Indonesia. This is especially true in the development of the financial sector. Trends show the real sector business development shar‟a is a great thought in the future that should be ready anticipated. Islamic banking and its products have been widely circulated in the community, in addition to the Islamic insurance and Islamic mutual funds have also started popping up like mushrooms in the rainy season. Continuity of Islamic economic system relies heavily on public trust which is the environment in which that demands openness and responsibility. Therefore, it is necessary support Islamic accounting personnel who are reliable and trustworthy in management of Islamic institution. Profession in the Islamic finance requires unique expertise and intellectual. Conventional accounting has been implemented has a lot of irrelevance with the principles of Islamic Shari‟a. That‟s because conventionalaccounting birth of the capitalist economic shari‟a.